Avaliação da influência do acompanhamento farmacoterapêutico e da terapia insulínica sobre a qualidade de vida, adesão ao tratamento e estresse oxidativo em pacientes com diabetes mellitus tipo 2 - Meriguete, Angélica Marchesi Lira (2018)
The practices of Pharmaceutical Care in Brazil are structured to promote medication adherence and quality of life, especially relevant in the context of type 2 diabetes mellitus (T2DM), which represents a growing problem of global health. It is a chronic metabolic disorder characterized by an increase in oxidative stress, which is related to the appearance of its main complications. T2DM is related to long and complex treatments, presence of comorbidities and complications which, together interfere negatively in the adherence to therapy. There are reports in the literature that the application of pharmaceutical care services has brought benefits on metabolic control and improved medication adherence of individuals with type 2 diabetes. In this study, it was evaluated if the pharmacotherapeutic follow-up performed for six months in patients with type 2 diabetes mellitus interferes in metabolic control, treatment adherence, quality of life and levels of pro and antioxidant species, besides the influence of insulin therapy on these parameters. Data collection was conducted before and after the six months of follow-up. 75 patients completed the study, 44 in the non-insulin therapy group and 31 in the insulin therapy group. After follow-up, an improvement in medication adherence was observed in the two groups. Similarly, there was a significant increase in the quality of life scores (p<0.0001) for the total sample. The physical domain of the insulin therapy group showed no change between the period (p = 0.052). In the oxidative stress parameters evaluated, there was a decrease in nitric oxide levels in both groups (p<0.0001) and an increase in superoxide dismutase concentration for the group with insulin therapy (p=0.0048). These results show that the proposed pharmacotherapeutic followup positively influenced on the medication adherence, quality of life and oxidative stress levels, and therefore, may contribute to delay the onset of the main chronic complications of the disease